If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2y + -10x + 5 = 0 Reorder the terms: 5 + 7x + -10x + 2y = 0 Combine like terms: 7x + -10x = -3x 5 + -3x + 2y = 0 Solving 5 + -3x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -3x + -5 + 2y = 0 + -5 Reorder the terms: 5 + -5 + -3x + 2y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x + 2y = 0 + -5 -3x + 2y = 0 + -5 Combine like terms: 0 + -5 = -5 -3x + 2y = -5 Add '-2y' to each side of the equation. -3x + 2y + -2y = -5 + -2y Combine like terms: 2y + -2y = 0 -3x + 0 = -5 + -2y -3x = -5 + -2y Divide each side by '-3'. x = 1.666666667 + 0.6666666667y Simplifying x = 1.666666667 + 0.6666666667y
| 3(x-4)=2x-6 | | 12x(x-9)=0 | | 2(2x-3)=3(x-10) | | -5X+12=5X^2-12 | | N^3+n^2-6n=0 | | 14-7x=43-14x | | 2n^2+12n+15=-3 | | 2n^2+12n+15=3 | | 2n^2+n-120=0 | | 10x^2n+47xny+42y^2n=0 | | 5g+15=2g | | -4x^3-2x+1=0 | | 6x+38=14 | | 27u^2+54uv-21v^2=0 | | 1x-2y-3z=0 | | Y^2+4Y+11=0 | | (2x-3)(x^2-5x+3)=0 | | -8-3c=19 | | ln^2x+lnx=12 | | 10x^2-21x+2=0 | | 4x-12=-30 | | 144x^2-96x-84=0 | | s^2d^2+9sd+14= | | 2-ln(3-x)=0 | | 9x^2y^2-12x^2y^2-3x^2y^2= | | a^3+1000b^3=0 | | 3e^3=10 | | 4x^2-72x+299=0 | | 20x+30(100-x)=2350 | | 4(x)=215 | | x^3+14x^2=-49x | | x^3+14x^2=-49 |